MISSIO DEI : PERAN GEREJA SEBAGAI MISI ALLAH DI ERA MODERN - Deivy Gebby Lemeng (PASOLO: Jurnal Ilmu Teologi dan Pendidikan Kristen, 2026)
This article discusses the concept of Missio Dei, or the Mission of God, as a theological foundation for the church's role in the modern era. Missio Dei asserts that mission is a divine initiative rooted in the nature of the Triune God and encompasses all creation and aspects of human life, extending beyond mere church activities. Amidst the complexities of the modern era, characterized by digital technological advancements, waves of globalization, and the emergence of secularism, postmodernism, and consumerism, the church faces significant challenges and opportunities. This report outlines how these characteristics of the modern era fundamentally influence the church's mission implementation, including triggering an identity crisis among adolescents. Therefore, a holistic and contextual mission approach is needed, integrating pastoral education, active involvement in social justice, and strategic utilization of digital technology. This report aims to provide a robust theological framework and adaptive practical strategies, enabling the contemporary church to strengthen its identity and relevance in effectively carrying out Missio Dei amidst changing times.